Pediatric and Adolescent Sports Traumatology - Guzzanti, Vincenzo; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2014)
This handy volume focuses on the evaluation and treatment of a wide range of sports injuries, in relation to the Tanner stage of sexual development in young athletes. Recognized leaders in each subspecialty illustrate their own treatment preferences, and a series of detailed chapters address the injuries likely to be encountered in different parts of the body, including the spine, shoulder, elbow, wrist and hand, hip, knee, ankle, and feet. Among the topics that receive particular attention are epiphyseal-physeal injuries, the still controversial issue of capsular ligament tears and the impact of their treatment on joint and bone development, and stress syndromes of the musculoskeletal system. Helpful algorithms covering the diagnosis and treatment of ligament tears are included, and advice is provided on when to return an athlete to training. One chapter is devoted to non-sports-related pathologies that have to be considered in the differential diagnosis of sports injuries in adolescents. Written by a multidisciplinary team of experts, this volume will be an excellent guide in diagnosis and in evaluating the impact of treatments for all professionals dealing with young athletes; orthopedic surgeons, physiotherapists, general practitioners and athletic trainers.
1 Basic science and injury in growing athletes: Cartilage, Menisci and Bone -- 2 Muscle, Tendon and Ligament -- 3 Evaluation of the pediatric and adolescent athlete -- 4 Overuse injuries -- 5 Physeal and epiphyseal cartilage injury -- 6 The Spine: Sports-related pathology -- 7 The Shoulder: skeletal injuries and ligamentous instability -- 8 The Elbow: Ligamentous and skeletal injuries -- 9 Wrist and Hand: Ligamentous and skeletal injuries -- 10 The Hip: Femoro-acetabular Impingement -- 11 The Knee: Ligamentous tears -- 12 Meniscal Lesions -- 13 Osteochondritis Dissecans of the Knee -- 14 Patello-femoral disorders -- 15 Osteochondritis Dissecans of the Talus -- 16 Acute ligamentous tears of the Ankle -- 17 Chronic instability of the Ankle -- 18 Foot Abnormalities and Pathologies -- 19 Non-sports-related pathologies in young athletes -- 20 Imaging and techniques.
Keywords: Medicine; Emergency medicine; Sports medicine; Medicine & Public Health; Sports Medicine; Primary Care Medicine